Preventing muscle wasting: pro‐insulin C‐peptide prevents loss in muscle mass in streptozotocin‐diabetic rats. Issue 2 (6th March 2023) - Maurotti, Samantha; Pujia, Roberta; Galluccio, Angelo; Nucera, Saverio; Musolino, Vincenzo; Mare, Rosario; Frosina, Miriam; Noto, Francesca Rita; Mollace, Vincenzo; Romeo, Stefano; Pujia, Arturo; Montalcini, Tiziana
Abstract: Background: C‐peptide therapy exerts several positive actions on nerves, vasculature, smooth muscle relaxation, kidney function and bone. To date, the role of C‐peptide in preventing type 1 diabetes‐related muscle atrophy has not been investigated. Our aim was to evaluate if C‐peptide infusion prevents muscle wasting in diabetic rats. Methods: Twenty‐three male Wistar rats were randomly divided into three groups: normal control group, diabetic group and diabetic group plus C‐peptide. Diabetes was induced by streptozotocin injection, and C‐peptide was administered subcutaneously for 6 weeks. The blood samples were obtained at baseline, before streptozotocin injection and at the end of the study to assess C‐peptide, ubiquitin and other laboratory parameters. We also tested the ability of C‐peptide to regulate the skeletal muscle mass, the ubiquitin–proteasome system, the autophagy pathway as well as to improve muscle quality. Results: C‐peptide administration reversed hyperglycaemia ( P  = 0.02) and hypertriglyceridaemia ( P  = 0.01) in diabetic plus C‐peptide rats compared with diabetic control rats. The diabetic‐control animals displayed a lower weight of the muscles in the lower limb considered individually than the control rats and the diabetic plus C‐peptide rats ( P  = 0.03; P  = 0.03; P  = 0.04; P  = 0.004, respectively). The diabetic‐control rats presented a significantly higher serum concentration of ubiquitin compared with the diabetic plus C‐peptide and the control animals ( P  = 0.02 and P  = 0.01). In muscles of the lower limb, the pAmpk expression was higher in the diabetic plus C‐peptide than the diabetic‐control rats (in the gastrocnemius, P  = 0.002; in the tibialis anterior P  = 0.005). The protein expression of Atrogin‐1 in gastrocnemius and tibialis was lower in the diabetic plus C‐peptide than in diabetic‐control rats ( P  = 0.02, P  = 0.03). After 42 days, the cross‐sectional area in the gastrocnemius of the diabetic plus C‐peptide group had been reduced by 6.6% while the diabetic‐control rats had a 39.5% reduction compared with the control animals ( P  = 0.02). The cross‐sectional area of the tibialis and the extensor digitorum longus muscles was reduced, in the diabetic plus C‐peptide rats, by 10% and 11%, respectively, while the diabetic‐control group had a reduction of 65% and 45% compared with the control animals (both P  < 0.0001). Similar results were obtained for the minimum Feret's diameter and perimeter. Conclusions: C‐peptide administration in rats could protect skeletal muscle mass from atrophy induced by type 1 diabetes mellitus. Our findings could suggest that targeting the ubiquitin–proteasome system, Ampk and muscle‐specific E3 ubiquitin ligases such as Atrogin‐1 and Traf6 may be an effective strategy for molecular and clinical intervention in the muscle wasting pathological process in T1DM.